2022
DOI: 10.3390/polym14214517
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microcrystalline Cellulose on the Properties of PBAT/Thermoplastic Starch Biodegradable Film with Chain Extender

Abstract: Poly (butylene adipate-co-terephthalate) (PBAT) is a fully biodegradable polymer with toughness and ductility. It is usually compounded with thermoplastic starch (TPS) to balance the cost for manufacturing biodegradable films such as disposable plastic bags. However, blending with TPS reduces valuable tensile strength, which limits the bearing capacity of PBAT film. In this study, microcrystalline cellulose (MCC) was employed as a reinforcement to strengthen the PBAT/TPS biodegradable film. The effect of MCC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As the more MFC added, the more weight loss ratio obtained at around 400°C. In addition, Figure 2a shows that a new thermal decomposition stage occurs at around 350°C when adding 5 or 10 g of MFC, this phenomenon shows that the addition of MFC has a certain effect on the thermal stability of the composite films 22 . However, in Figure 2b, the amount of SPI has no effect or less effect on the thermal stability of composite films, and the weight‐loss peak also appeared at 400°C.…”
Section: Resultsmentioning
confidence: 95%
“…As the more MFC added, the more weight loss ratio obtained at around 400°C. In addition, Figure 2a shows that a new thermal decomposition stage occurs at around 350°C when adding 5 or 10 g of MFC, this phenomenon shows that the addition of MFC has a certain effect on the thermal stability of the composite films 22 . However, in Figure 2b, the amount of SPI has no effect or less effect on the thermal stability of composite films, and the weight‐loss peak also appeared at 400°C.…”
Section: Resultsmentioning
confidence: 95%
“…44,[67][68][69] The incorporation of SEW4 fibers in the PBAT matrix had practically no influence on the thermal stability of the materials, with T onset , T 10% , and T max values remaining practically equal to those of neat PBAT. Some authors reported that excessive fiber contents may inhibit the chain slip because of agglomeration, leading to slightly weaker thermal stabilities 70,71 ; however, the results found were still similar to the neat PBAT.…”
Section: Thermogravimetric Analysismentioning
confidence: 85%
“…According to Fig. 8, it can be observed that PBAT has ve characteristic re ection peaks at 16.3°, 17.4°, 20.2°, 23.1° and 25.0°, corresponding to (011), ( 010), ( 110), ( 100) and (111) crystal planes, indicating that PBAT is an α-type trigonal stacking structure [21]. The diffraction angle of llers (K-BP, K-WP and K-CP) should show 2θ 22.5° of cellulose [22], which overlaps with the PBAT crystalline peak.…”
Section: Enhancement Crystallinity Of Pbatmentioning
confidence: 99%